Development and validation of a dynamic nomogram based on conventional ultrasound and contrast-enhanced ultrasound for stratifying the risk of central lymph node metastasis in papillary thyroid carcinoma preoperatively - Chen, Qiyang; Liu, Yujiang; Liu, Jinping; Su, Yuan; Qian, Linxue; Hu, Xiangdong (Frontiers in Endocrinology, 2023)
Purpose To develop and validate a dynamic nomogram by combining conventional ultrasound (US) and contrast-enhanced US (CEUS) to preoperative evaluate the probability of central lymph node metastases (CLNM) for patients with papillary thyroid carcinoma (PTC). Methods A total of 216 patients with PTC confirmed pathologically were included in this retrospective and prospective study, and they were divided into the training and validation cohorts respectively. Each cohort was divided into the CLNM (+) and CLNM (-) groups. The least absolute shrinkage and selection operator (LASSO) regression method was applied to select the most useful predictive features for CLNM in the training cohort, and these features were incorporated into a multivariate logistic regression analysis to develop the nomogram. The nomogram's discrimination, calibration, and clinical usefulness were assessed in the training and validation cohorts. Results In the training and validation cohorts, the dynamic nomogram (https://clnmpredictionmodel. shinyapps.io/PTCCLNM/) had an area under the receiver operator characteristic curve (AUC) of 0.844 (95% CI,0.755–0.905) and 0.827 (95% CI, 0.747–0.906) respectively. The Hosmer-Lemeshow test and calibration curve showed that the nomogram had good calibration (P=0.385, P=0.285) . Decision curve analysis (DCA) showed that the nomogram has more predictive value of CLNM than US or CEUS features alone in a wide range of high-risk threshold. The Nomo-score 0.428 as the cut-off value had a good performance to stratify high-risk and low-risk groups. Conclusion A dynamic nomogram combining US and CEUS features can be applied to risk stratification of CLNM in patients with PTC in clinical practice.